Hormonal, antioxidant, and body composition differences in national level male athletes: a comparative study of aerobic and anaerobic training - Jaradat, Manar Burhan; Maghayreh, Eyyad; Husain, Waqar; Trabelsi, Khaled; Amawi, Adam; Jahrami, Haitham; Ghazzawi, Hadeel Ali (Frontiers in Sports and Active Living, 2025)
BackgroundCompetitive athletes exhibit distinct physiological adaptations depending on their sport type and training techniques. These variations influence body composition, hunger-regulating hormones, and antioxidant defense mechanisms, which collectively impact performance, recovery, and progression. This study aimed to compare body composition, serum levels of ghrelin, leptin, and glutathione (GSH), and their interrelationships in national level male athletes engaged in aerobic and anaerobic sports.MethodsTwenty competitive athletes (aged 17–38 years) were evenly divided into aerobic (AS) and anaerobic (AnS) sports groups. Body composition—including skeletal muscle mass (SMM), fat-free mass (FFM), fat mass (FM), and percent body fat (PBF)—was assessed using bioelectrical impedance analysis (BIA). Blood samples were collected after 8 h of fasting to measure ghrelin, leptin, and GSH levels. Dietary intake was evaluated using a 24-h recall. Group differences were analyzed using the Mann–Whitney U-test, and correlations were determined using Spearman's rank correlation, with statistical significance set at p < 0.05.ResultsThe AnS group displayed significantly higher SMM and FFM compared to the AS group (p < 0.05). Ghrelin levels were significantly lower in the AS group (p < 0.05), while leptin and GSH levels did not differ significantly between groups. Positive correlations were observed between ghrelin and both SMM and FFM (r = 0.585, p = 0.007), and between GSH and dietary protein intake (r = 0.476, p = 0.03).ConclusionsAnaerobic exercise enhances muscle mass, while aerobic exercise supports appetite suppression. Limitations include the small sample size and reliance on 24-h dietary recall. Future research should use larger, more diverse samples and explore combined training effects. Recommendations include incorporating resistance training into aerobic regimens to optimize muscle mass and monitoring protein intake to support antioxidant defense.